GAMBARAN PENGGUNAAN OBAT KUMUR EKSTRAK TANAMAN SERAI (CYMBOPOGON NARDUS) TERHADAP PENURUNAN INDEKS PLAK PADA MAHASISWA KSO JURUSAN KEPERAWATAN GIGI POLTEKKES MEDAN - intan aritonang; yetti lusiani; hasny hasny (Poltekkes Kemenkes Medan, 2016)
Mouthwash (gargarisma) is medicinal preparation of solution which is usually thick so that should be liquefied before using it. Plaque is soft sediment which sticks tightly on tooth surface and can cause caries and periodontal disease. Plaque index is an index which is used to measure plaque score based on location and the amount of plaque on the edge of gum.The research was a descriptive survey which was aimed to find out the decrease in plaque index by using mouthwash from citronella grass (Cymbopogon nardus) in the KSO students, Dental Hygiene Department, Poltekkes, Medan. The result of the direct examination showed that the mean plaque index before gargling with mouthwash of citronella grass extract was 0.34 and after gargling with mouthwash of citronella grass extract was 0.21. Meanwhile, the mean plaque index before gargling with plain water was 0.31 and after gargling with plain water was 0.25. Thus, the decrease in the plaque index and after gargling with plain water was 0.06.The conclusion was that gargling with mouthwash of citronella grass could decrease plaque index. It is recommended that the KSO students always maintain their dental and oral hygiene.